PINJAMAN LUAR NEGERI PEMERINTAH DAN PERTUMBUHAN EKONOMI: PENGARUH DINAMIK LANGSUNG DAN TIDAK LANGSUNG DI INDONESIA PERIODE 1970-2008 - Marno Kastowo (Indonesian Journal of Economics and Business, 2012)
Does GFD have significant effect on economic growth? This question can’t be answered solely based on theory and previous empirical study due to the  existence of theoretical controversy and empirical ambiguity. The purpose of this research is to build model which has ability to explain the direct and indirect dynamic effect of GFD on economic growth.  The quantitative analysis was conducted with four simultaneous structural equations estimated by TSLS. The economic growth model in this research is specified as a dynamic model (partial adjustment) that allow us to make short run and long run multiplier analysis.              This research shows that GFD receipt has insignificant direct effect and positive indirect effect on economic growth, while GFD payment has negative direct and indirect effect. The negative effect of the GFD payment is larger than the positive effect of the GFD receipt. It is proved that GFD has long run effect (multiplier)on economic growth, the total long run multiplier reachs 123,06% of the short run multiplier. Practically, the long run multiplier will be end up in  four  years.